N‐glycosylation by N‐acetylglucosaminyltransferase V enhances the interaction of CD147/basigin with integrin β1 and promotes HCC metastasis. Issue 1 (30th March 2018) - Cui, Jian; Huang, Wan; Wu, Bo; Jin, Jin; Jing, Lin; Shi, Wen‐Pu; Liu, Zhen‐Yu; Yuan, Lin; Luo, Dan; Li, Ling; Chen, Zhi‐Nan; Jiang, Jian‐Li
Abstract: While the importance of protein N‐ glycosylation in cancer cell migration is well appreciated, the precise mechanisms by which N ‐acetylglucosaminyltransferase V (GnT‐V) regulates cancer processes remain largely unknown. In the current study, we report that GnT‐V‐mediated N‐ glycosylation of CD147/basigin, a tumor‐associated glycoprotein that carries β1, 6‐ N ‐acetylglucosamine (β1, 6‐GlcNAc) glycans, is upregulated during TGF‐β1‐induced epithelial‐to‐mesenchymal transition (EMT), which correlates with tumor metastasis in patients with hepatocellular carcinoma (HCC). Interruption of β1, 6‐GlcNAc glycan modification of CD147/basigin decreased matrix metalloproteinase (MMP) expression in HCC cell lines and affected the interaction of CD147/basigin with integrin β1. These results reveal that β1, 6‐branched glycans modulate the biological function of CD147/basigin in HCC metastasis. Moreover, we showed that the PI3K/Akt pathway regulates GnT‐V expression and that inhibition of GnT‐V‐mediated N‐ glycosylation suppressed PI3K signaling. In summary, β1, 6‐branched N‐ glycosylation affects the biological function of CD147/basigin and these findings provide a novel approach for the development of therapeutic strategies targeting metastasis. © 2018 The Authors. The Journal of Pathology published by John Wiley & Sons Ltd on behalf of Pathological Society of Great Britain and Ireland.